Efforts to Develop Taman Gumi Banten Forest in Wanagiri Village as Forest Tourism Through Environmental Empowerment of Internal Forest Resources - Nyoman Wijana; Sanusi Mulyadiharja; I Made Oka Riawan (Jurnal Pendidikan Biologi Undiksha, 2022)
This study aims to explore the potential of forest natural resources in the forest of Taman Gumi Banten, both regarding the potential of ethnobotany and ethnoecology in an effort to develop forest tourism. The location of this research is in the forest of Taman Gumi Banten, Wanagiri Village, Sukasada District, Buleleng Regency. This type of research is included in the type of exploratory research. The population of this research is all plant species in the forest of Taman Gumi Banten, while the research sample is plant species covered by the square. In an effort to utilize the forest of Taman Gumi Banten as forest tourism, interviews, questionnaires, and observations were conducted. Data were analyzed using ecological statistics and descriptive analysis. The conclusion from the results of this study is the potential of forest natural resources in the forest of Taman Gumi Banten, both regarding its ethnobotany and ethnoecological potential, can be used as components that contribute to the development of forest tourism. The existing potential is in the form of information about plant species that make up the forest of Taman Gumi Banten, diversity of plant species, SDR and IV, utilization, processing, and products produced from plant species in the forest, distribution maps of plant species, and forest conservation based on local wisdom.